Tracés à l’épreuve de la parité. Entretien croisé avec Sonia Goldblum, Yaël Kreplak, Cécile Lavergne et Lucy Tangy - Anaïs Albert; Christelle Rabier; Sonia Goldblum; Yaël Kreplak; Cécile Lavergne; Lucie Tangy (Tracés, 2018)
In the aftermath of the publishing of Tracés’s special issue (no 32, 2017) contextualizing the translation of Natalie Zemon Davis’ paper about “Women and the world of the Annales” and the answer provided by the Annales’ editor-in-chief, Tracés invites a retrospective and critical analysis on the part played by the women who first belonged to the editorial board of the journal. The interview is introduced by a quantitative discussion, drawn from the journal data for 2007-2018, of the male domination over the publication, although gender studies were given significant room. The interview given by the first four female scholars to join the editorial board provides evidence that parity – although imperfect – was achieved thanks to the combined efforts of women and a few men. The interview retraces the four women’s motivations to take part of the journal’s board, their roles in the editorial process, their interactions within the editorial board, and it addresses the editorial choices which they took part of.